PO026 Hypercalcaemia and hypomagnesaemia causing posterior reversible encephalopathy syndrome. (1st December 2017) - Williamson, J; Panicker, J
Abstract : A 56-year-old lady was admitted with a history of acute confusion, drowsiness and seizures. She had a past history of learning disability, epilepsy and osteoporosis On examination she was confused and disoriented. She was normotensive and there was no focal neurological deficit. MRI brain demonstrated symmetrical signal change in the parietal and occipital lobes on FLAIR sequences with mild diffusion restriction. MRA revealed no evidence of vasoconstriction. CSF constituents were within normal limits and blood tests showed normal inflammatory markers alongside hypercalcemia (3.74 mmol/L) and hypomagnesemia (0.4 mmol/L). She was discovered to be taking Vitamin D and Calcium supplements for osteoporosis and her carers reported concern that she was taking above than the recommended dose. A screen for alternative causes of hypercalcaemia was unrevealing. Calcium supplements were discontinued and she received IV Bisphosphonates. With time her calcium levels normalised and confusion resolved. A repeat MRI, performed two weeks later, demonstrated resolution of the posterior signal change. PRES (Posterior reversible encephalopathy syndrome) has several risk factors including hypertension, organ transplantation and immunosuppressant drugs. Both hypercalcemia and hypomagnesemia are recognised as rarer causes of PRES. This case highlights the importance of excluding these correctable rarer causes, especially in patients with normal blood pressure.